Current Status of Projects for Risk Management in official educational institutions in La Comuna 8 of the City of Villavicencio, Department of Meta - Romero Lopez, Francisco Antonio; Ramirez Espitia, Jose (Corporación Universitaria Americana, 2019)
This article seeks to evaluate the degree of knowledge that refers to the people who are part of the official educational institutions of the Commune 8 of Villavicencio (Meta), as opposed to risk management. The research focused on its eight institutions. The results are intended to encourage regional and national studies on the status of risk management projects, ensuring that learning spaces meet the results of care and emergencies, improving the response capacity of teachers, administrative and students. The implementation of projects for risk management, educational institutions, the agenda of territorial entities, activities to prevent and avoid situations of risk that can lead to an emergency or the loss of human and material lives.